(untitled) (Research, Society and Development, 2021)
Cerebral palsy (CP) is the most common motor disability in childhood, and as far as we know, there are no biometric studies that have evaluated CP and oral health (OH) on a global level. The aim of this study was to present the worldwide research trends in studies of OH in persons with CP, using bibliometric analysis. Through bibliographic information on publications about OH and CP was obtained in the PubMed database, from 1956 to 2021. The extracted data included periodical, title, year of publication, authors, citations, impact factor, key words, country, most cited publications, and study design. A total of 567 articles were published and indexed in PubMed up until 6/28/2021. The data showed a constant growth and an exponential increase in the number of publications. The articles were written in 17 different languages, and 232 (90.63%) articles were in English. Among the 111 Periodicals, Special Care in Dentistry contributed the most to scientific research with 30 articles (17.3%). Brazil (25%) and the United States (17.24%) were the countries with the highest number of publications. Observational studies were the most frequent types of articles (76.29%), followed by case reports (13.36%). It was concluded that this current network analysis indicates that although there is a significant growth in the number of publications about OH in persons with CP, it is important to increase the number of interventional randomized clinical trial studies, to include this population in high-impact oral health investigations around the world.